Non-fragile H∞ control for body slip angle of electric vehicles with onboard vision systems: The dynamic event-triggering approach - Tan, Hailong; Shen, Bo; Li, Qi; Shu, Huisheng (Journal of the Franklin Institute, 2020)
This paper is concerned with the dynamic event-triggered non-fragile H∞ control problem for the body slip angle of electric vehicles subject to parameter variations of vehicle controllers. Dynamics of electric vehicles with an onboard vision system is characterized by a linear model in which the body slip angle, the yaw rate, the lateral offset at the preview point and the vehicle heading angle are chosen as state variables. To reduce the energy consumption in signal transmission, a dynamic event-triggering mechanism is adopted to manage the data transmission between sensors and vehicle controllers. Our aim is to design a non-fragile event-triggered controller such that, for all possible parameter variations in controller gains, all the system states are asymptotically stable and the H∞ performance requirement is met. With the help of the Lyapunov theory, an existence condition of the desired controller is established first and then the desired controller gains are designed in terms of a feasible solution to a matrix inequality. Finally, the effectiveness of the proposed non-fragile H∞ control approach is verified in the electric vehicles.